2010
DOI: 10.1111/j.1365-2133.2010.09989.x
|View full text |Cite
|
Sign up to set email alerts
|

Activating BRAF mutations in eruptive melanocytic naevi

Abstract: Our results implicate mutational activation of the BRAF–MAPK pathway as a factor in development of EMN in the setting of 6-MP treatment. The mechanism leading to development of EMN in this, and potentially other patients, may relate to synergistic mutagenic effects of thioguanines and ultraviolet (UV) A. Together with the documented importance of BRAF mutations in melanoma development and maintenance, these findings highlight the importance of UVA protection, especially in patients treated with thiopurines suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
1
16
0
1
Order By: Relevance
“…It is also well documented that nevi can enlarge or erupt de novo in large numbers under immunosuppresion. Such eruptive nevi also frequently have BRAF mutations and favor sun-exposed sites, indicating that the initiating mechanisms are identical to other acquired nevi (47). In a liver model, hepatocytes that became senescent due to oncogenic RAS were effectively eliminated by immune cells (48).…”
Section: Melanocytic Neoplasms Originating From Epithelial Melanocytesmentioning
confidence: 96%
“…It is also well documented that nevi can enlarge or erupt de novo in large numbers under immunosuppresion. Such eruptive nevi also frequently have BRAF mutations and favor sun-exposed sites, indicating that the initiating mechanisms are identical to other acquired nevi (47). In a liver model, hepatocytes that became senescent due to oncogenic RAS were effectively eliminated by immune cells (48).…”
Section: Melanocytic Neoplasms Originating From Epithelial Melanocytesmentioning
confidence: 96%
“…The purpose of the study was to investigate the molecular mechanisms underlying the development of eruptive melanocytic nevi (EMN) in a white male patient receiving 2 years of 6-mercaptopurine (6-MP) therapy for ulcerative colitis [1]. Over the course of the 6-MP treatment, the patient experienced an explosive growth of >200 melanocytic lesions on intermittently sun-exposed body sites.…”
Section: Summary Of Methods and Resultsmentioning
confidence: 99%
“…It remains plausible that this systemic population of susceptible nevus progenitor cells was derived from a single cell. Supporting evidence includes a recent case report by Sekulic et al that demonstrated a BRAF V600E mutation in 17 of 20 eruptive nevi removed from a single patient who was being treated with 6-Mercaptopurine [21]. Although the authors interpreted their results to imply that treatment with this immunosuppressive agent increases mutational frequency, it is also possible that most of these nevi share a monoclonal origin.…”
Section: Supporting Evidencementioning
confidence: 98%